Bio‐Inspired Synthesis of an Ordered N/P Dual‐Doped Porous Carbon and Application as an Anode for Sodium‐Ion Batteries. Issue 63 (19th October 2017) - Qiao, Yun; Han, Ruimin; Liu, Yang; Ma, Mengyue; Cheng, Xiaoguang; Li, Qingling; Yue, Hongyun; Cao, Zhaoxia; Zhang, Huishuang; Yang, Shuting
Abstract: Carbonaceous materials are one of the most promising anode materials for sodium‐ion batteries, because of their abundance, stability, and safe usage. However, the practical application of carbon materials is hindered by poor specific capacity and low initial Coulombic efficiency. The design of porous structure and doping with heteroatoms are two simple and effective methods to promote the sodium storage performance. Herein, the N, P co‐doped porous carbon materials are fabricated using renewable and biodegradable gelatin as carbon and nitrogen resource, phosphoric acid as phosphorus precursor and polystyrene nanospheres as a template. The product can deliver a reversible capacity of 230 mA h g −1 at a current density of 0.2 A g −1, and even a high capacity of 113 mA h g −1 at 10 Ag −1 . The enhanced sodium storage performance is attributed to the synergistic effect of the porosity and the dual‐doping of nitrogen and phosphorus. Abstract : I got the power : The porous and well‐arranged 3D structure affords more open channels for electrolyte permeation and more active sites for the insertion/extraction of Na + . The synergistic effect of nitrogen and phosphorus dopants establishes a well‐conductive network and enlarges the interlayer distance. The product can deliver a reversible capacity of 230 mA h g −1 at a current density of 0.2 A g −1 and even a high capacity of 113 mA h g −1 at 10 A g −1 .